Pengaruh Tinggi Reservoir dan Debit Masukan terhadap Efisiensi Pompa Hidram - Syariful Hadi, Muhammad; Nugroho, Setyo; Ghani Safitra, Arrad; Ghani Safitra, Arrad (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Water is a fundamental human need. One effort to obtain a constant water supply is by pumpingmethod. The Hydram pump is one of the alternatives that can be used to meet these needs. Inaddition to cost-effective, this pump is also very simple in manufacturing, assembling, andoperation. The installation components of the hydram pumps consist of water tanks, input pipes,output pipes, exhaust valves, sender valves, and air tubes. The workmanship of this final taskwill be measured the number of discharge pumping, tapping the exhaust valve, pressuredischarge, D'aubuisson efficiency, and hydram pump efficiency to the height variation of thereservoir and discharge input. On the workmanship of this final task will be used the hydrampump with specification: 1-inch input pipe diameter, the output pipe diameter of 0.75 inches, thediameter of air tube 2 inch, high air tube 0.75 m, and heavy exhaust valve load 0.4 kg.Variations in working conditions that will be tested on the Hydram pump are high reservoir (1m, 1.25 m, 1.5 m) and discharge input (10 LPM, 12 LPM, 14 LPM). From the experiments thathave been carried out the highest pumping discharge of 2.1 LPM at an altitude of 1.5 m with aninput discharge of 14 LPM. The large pressure discharge value that occurs during the workingcycle of the hydram pump is directly proportional to the reservoir height. Best hydram pumpperformance is obtained at 1.5 m altitude variation with 14 LPM input discharge where theefficiency of D'aubussion is 44.06% and the efficiency of the Hydram pump 29.91%.